2021
DOI: 10.1111/caim.12428
|View full text |Cite
|
Sign up to set email alerts
|

Platform‐driven innovation: Unveiling research and business opportunities

Abstract: An increasing number of businesses have adopted a platform business model. Platform companies such as Airbnb, Amazon, Facebook, Google, Salesforce and Uber are amongst the world's most valuable companies and have revolutionized their respective industries. But what are platforms? Is there a unique definition? How do they innovate, and what is their place in the innovation literature? This editorial article considers those questions. First, it provides an overview of platform definitions, their evolution, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…Uber, which was initially considered a luxury service with premium black cars, has become relevant to many people because it opened up opportunities for people to become drivers. Uber discloses transactions that may occur in the market, a transaction that has never happened before; they reveal to customers and service providers the potential existence of unexploited markets (Trabucchi et al, 2021).…”
Section: Factors Affecting Uber's Failure In the Southeast Asian Marketmentioning
confidence: 99%
See 1 more Smart Citation
“…Uber, which was initially considered a luxury service with premium black cars, has become relevant to many people because it opened up opportunities for people to become drivers. Uber discloses transactions that may occur in the market, a transaction that has never happened before; they reveal to customers and service providers the potential existence of unexploited markets (Trabucchi et al, 2021).…”
Section: Factors Affecting Uber's Failure In the Southeast Asian Marketmentioning
confidence: 99%
“…Meanwhile, the gig economy is a working system that prioritizes individual flexibility to schedule their work and personal life (Gandini, 2018). Platforms related to digital innovation will significantly influence or even transform markets, industries, and society (Trabucchi, Buganza, Muzellec, & Ronteau, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Since platforms thrive on their participants, their motivation is essential, which—especially on two‐sided platforms—poses complex challenges manifoldly discussed in the literature (Caillaud & Jullien, 2003). Research has identified several strategies to ensure the successful establishment and use of digital platforms (Trabucchi et al, 2021; Trischler et al, 2021).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Research has identified several strategies to ensure the successful establishment and use of digital platforms (Trabucchi et al, 2021;Trischler et al, 2021).…”
Section: Motivation Related To Online Ideation Platforms and The Chan...mentioning
confidence: 99%
“…Furthermore, comprehension is gained of platform capabilities that address transport management and support service innovations based on digital technologies through a unified understanding. Although scholars have broadly examined DPs and explored platform innovations for digital business models (e.g., Dmitriev & Plastunyak, 2019 ; Tiwana, 2013 ; Trabucchi et al, 2021 ), more comprehensive insights into cloud-enabled road freight business are recommended to elaborate on the understanding of platforms for specific business industries (Pauli et al, 2021 ). To this end, a typology facilitates digital platform research activities in transport logistics by providing a domain-specific framework for the abstracted activities that RFTM tools should support.…”
Section: Introductionmentioning
confidence: 99%